2009
DOI: 10.1038/nrrheum.2009.81
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial progenitor cell dysfunction in rheumatic disease

Abstract: Rheumatic disease is characterized by inflammation and endothelial dysfunction, which contribute to accelerated atherosclerosis. Circulating endothelial progenitor cells (EPCs) can restore dysfunctional endothelium and thereby protect against atherosclerotic vascular disease. The number and function of EPCs are, however, affected in rheumatic diseases such as psoriatic arthritis, rheumatoid arthritis, systemic lupus erythematosus, systemic sclerosis, and antineutrophil cytoplasmic autoantibody-associated vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 87 publications
(140 reference statements)
0
48
0
2
Order By: Relevance
“…33 However, the mechanisms underlying this pathogenetic correlation remain to be elucidated. Our results indicate that leukocyte ROS production, particularly by neutrophils, is significantly enhanced in BD patients.…”
Section: Discussionmentioning
confidence: 99%
“…33 However, the mechanisms underlying this pathogenetic correlation remain to be elucidated. Our results indicate that leukocyte ROS production, particularly by neutrophils, is significantly enhanced in BD patients.…”
Section: Discussionmentioning
confidence: 99%
“…To eliminate this difficult transition, we have always used human cells throughout our initial research. However, multiple studies have clearly demonstrated that donor age and health status can dramatically affect cell behavior [Phillips et al, 1994;Becerra et al, 1996;Michel et al, 1996;Mogford et al, 2002;Heeschen et al, 2004;Zhang et al, 2005;Garolla et al, 2009;Krenning et al, 2009;Westerweel and Verhaar, 2009]. Thus, the second translational step was to use age-and risk-matched human cells.…”
Section: Preclinical Studies With the Lifeline Tm Graftmentioning
confidence: 99%
“…Microvascular endothelial cells challenged with inflammatory stimuli expressed the membrane-bound form of KitL and recruited EPCs via a c-Kit-mediated activation of the Akt signaling pathway to inflamed endothelium (18). However, chronic inflammatory processes or excessive inflammatory stimuli have deleterious effects, resulting in decreased EPCs in the circulation (4,119,126). Low levels of circulating CD133=KDRþ EPC also predicted occurrence of coronary atherosclerosis in rheumatoid arthritis (134).…”
Section: Inflammatory Diseasesmentioning
confidence: 99%